HUBUNGAN TINGKAT KEMANDIRIAN DENGAN RISIKO JATUH PADA LANSIA DI WILAYAH KERJA PUSKESMAS PARIAMAN - SYAHRUL; FAJRI FEBRINI AULIA; HENY PUTRI CHANIA (Sekolah Tinggi Ilmu Kesehatan (STIKes) Piala Sakti Pariaman, 2026)
Elderly individuals are a vulnerable group who experience a decline in physical function, including independence in performing daily activities. This reduction in independence increases the risk of falls, which may affect their quality of life and raise morbidity and mortality rates. This study aimed to determine the relationship between independence level and fall risk among the elderly in the working area of the Pariaman Health Center in 2025. This research used a quantitative method with a cross-sectional design. The population consisted of all elderly individuals living in the working area of the Pariaman Health Center, with a total sample of 44 respondents selected using purposive sampling. The research instruments were the Activities of Daily Living (ADL) questionnaire to assess independence level and the Morse Fall Scale to measure fall risk. Data were analyzed using the Chi-Square test at a 95% confidence level (α = 0.05). The results showed that 52.3% of respondents were independent, 29.5% moderately dependent, and 18.2% heavily dependent. Regarding fall risk, 45.5% were at low risk, 29.5% had no risk, and 25% had high risk. Statistical analysis indicated a significant relationship between independence level and fall risk among the elderly (p = 0.004). The study concludes that the lower the level of independence, the higher the fall risk. Health workers are encouraged to promote elderly independence through regular physical activity and preventive fall-risk education programs. Keywords: independence level, fall risk, elderly